Risk Management in BOT - Dr. Deepa A. Joshi2, Sudhir Kumar1 (International Journal of Scientific Research and Management (IJSRM), 2016)
The significance of the road sector in India cannot be undervalued. It’s one in all the key factors within the economic and cultural progress of the nation.The growth of the infrastructure sector in India has been comparatively slow compared with the commercial and manufacturing sectors. The energy shortage, an inadequate transportation network, and an inadequate water system have caused a bottleneck within the country’s economic growth. The Build-Operate-Transfer (BOT) scheme is currently becoming one in all the prevailing ways that for infrastructure development in India to fulfill the requirements of India’s future economic growth and development. Risk management used as a tool in managing projects so as to reduce risk particularly for projects that involved an enormous amount of cash. In this paper, the factors liable for time overruns for BOT projects are known through a survey. Analysis of the data collected from experts is done by AHP. The relative importance and significance of those factors are investigated. The various types of risk encountered in BOT projects were investigated from the aspect of various key participants. The main purpose of this present work is to investigate critical risks related to Build-Operate-Transfer (BOT) projects in India